Influence of interlayer temperature on microstructure of 5183 aluminium alloy made by wire arc additive manufacturing. (22nd May 2021) - Derekar, Karan S.; Griffiths, David; Joshi, Sameehan S.; Lawrence, Jonathan; Zhang, Xiang; Addison, Adrian; Melton, Geoff; Xu, Lei
The variations in mechanical properties compared to the traditional processed (wrought) products, porosity formation, and solidification cracking are the primary concerns that may restrict industrial applications of wire arc additive manufacturing (WAAM) aluminium alloy products. Interlayer temperature is one of the crucial factors that can adversely affect the built quality and properties of material produced using WAAM. The paper aims at the possible effects of different interlayer temperatures on the geometry and microstructure of WAAM aluminium 5183 alloy as a function of varying heat input. For a given heat input, samples built using a higher interlayer temperature (100°C) showed wider and shorter layer deposits with increased penetration compared with lower interlayer temperature (50°C) samples. Microstructure of the chosen material revealed columnar grains at each layer and equiaxed grains at layer overlap position and at top layer. Interlayer temperature had a minor influence on deposit geometry and microstructure.